Left-right asymmetries in polarized lepton-lepton scattering - Montero, J. C. [UNESP]; Pleitez, V. [UNESP]; Rodriguez, M. C. [UNESP] (American Physical Society (APS), 1998)
Several parity-violating left-right asymmetries in Miller electron-electron and muon-muon scattering are considered in the context of the electroweak standard model at the tree level in fixed target and collider experiments. We show that in colliders the asymmetry with only one of the beams polarized is large enough to compensate the smaller cross section at high energies. We also show that these asymmetries are very sensitive to a doubly charged vector bilepton resonance but they are insensitive to scalar ones.